1999
DOI: 10.1002/(sici)1097-4547(19991215)58:6<752::aid-jnr3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Completion of myelin compaction, but not the attachment of oligodendroglial processes triggers K+ channel clustering

Abstract: The characteristic localization of ion channels is crucial for the propagation of saltatory conduction in myelinated nerves. Voltage-gated Na(+) channels are located at nodes of Ranvier while voltage-gated K(+) channels are mainly found at juxtaparanodal regions. Recently, a humoral factor secreted by oligodendrocytes has been reported to induce clustering of Na(+) channels in CNS axons. However, the molecular mechanisms for K(+) channel clustering as well as the role of oligodendrocytes are still uncertain. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The differential impact of myelination on Caspr and Kv1.2 subunit restoration may reflect different signaling mechanisms for their localization along axons. Although K ϩ channel juxtaparanodal localization is dictated by compact myelin, as was suggested previously (Baba et al, 1999), the formation of axoglial junctions is sufficient for Caspr paranodal localization. Reorganization of Caspr immunostaining in our studies sug- Figure 8.…”
Section: Discussionsupporting
confidence: 54%
“…The differential impact of myelination on Caspr and Kv1.2 subunit restoration may reflect different signaling mechanisms for their localization along axons. Although K ϩ channel juxtaparanodal localization is dictated by compact myelin, as was suggested previously (Baba et al, 1999), the formation of axoglial junctions is sufficient for Caspr paranodal localization. Reorganization of Caspr immunostaining in our studies sug- Figure 8.…”
Section: Discussionsupporting
confidence: 54%
“…Immunocytologic detection of Kv channels in the optic nerves has been performed so far only after P10 -P14 (Baba et al 1999;Rasband et al 1998Rasband et al , 1999 when the K ϩ channels are densely packed in juxtaparanodal regions. The present pharmacological data made it possible to identify DTX-I-sensitive channels at earlier ages (as early as P1) and to establish that the effects of DTX-I and KTX peak at around P12.…”
Section: Fig 9 Unmasking Of Paranodal Dtx-i-sensitive Kmentioning
confidence: 99%
“…Only two types of K ϩ channels have been pharmacologically identified so far to our knowledge in the adult rat optic nerve using this technique: one of these is sensitive to 4-AP and the other is sensitive to TEA . Based on immunocytologic detection data, Baba et al (1999) have reported that Kv1.1 and Kv1.2 ␣ subunits are diffusely distributed in mouse optic nerves at P10 and are sequestrated in juxtaparanodal regions during development. However, no electrophysiological studies were attempted to identify the variations in K ϩ expression during development and to compare the K ϩ channels present in CNS and PNS fibers.…”
mentioning
confidence: 99%
“…Additionally, there is a few colocalization between PSD-95 and NF-200 expressed in axons. As an attractive candidate for an axonal Kv1 channel binding partner, PSD-95 exhibits a high affinity interaction with the class I PDZbinding peptide motifs at the COOH termini of Kv1.1, Kv1.2, and Kv1.4 [24], suggesting that PSD-95 might be responsible for the clustering of Kv 1 channels at juxtaparanodes of myelinated axons [32,44].…”
Section: Discussionmentioning
confidence: 99%